Phenolic acids determination by HPLC-DAD-ESI/MS in sixteen different portuguese wild mushrooms species - Barros, Lillian (2010)
Analysis of phenolic compounds in sixteen Portuguese wild mushrooms species has been carried out by high-performance liquid chromatography coupled to photodiode array detector and mass spectrometer (HPLC–DAD–ESI/MS). No flavonoids were detected in the analysed samples, but diverse phenolic acids namely protocatechuic, p-hydroxybenzoic and p-coumaric acids, and two vanillic acid isomers were found and quantified. A related non-phenolic compound, cinnamic acid, was also detected in some samples, being the only compound found in Cantharellus cibarius (14.97 mg/kg, dry matter), Lycoperdon perlatum (14.36 mg/kg) and Macrolepiota procera (21.53 mg/kg). p-Hydroxybenzoic acid was found in the majority of the samples, being the most abundant compound in Agaricus silvicola (238.7 mg/kg). Ramaria botrytis showed the highest phenolic acids concentration (356.7 mg/kg) due to the significant contribution of protocatechuic acid (342.7 mg/kg).